ChemInform Abstract: Tetrahedral Framework Structures: Polymorphic Phase Transition with Reorientation of Hexagonal Helical Channels in the Zintl Compound Na2ZnSn5 and Its Relation to Na5Zn2+xSn10‐x. Issue 45 (14th October 2013) - Stegmaier, Saskia; Kim, Sung‐Jin; Henze, Alexander; Faessler, Thomas F.
Abstract Two modifications of the new title compound, hP‐Na2ZnSn5 (I) and tI‐Na2ZnSn5 (II) are prepared from the elements at 450 and 300 °C, respectively.